Peranan Guru PPKN dalam Mengimplementasikan Profil Pelajar Pancasila di SMP Negeri 4 Metro - Wibowo, M. Arief Satria; Pitoewas, Berchah; Putri, Devi Sutrisno (JURNAL KULTUR DEMOKRASI (JKD), 2023)
This research is to find out the role of Pancasila and civic education teachers in implementing Pancasila student profiles at junior high schools in State 4 Metro. The research method used in this research is a descriptive method with a quantitative approach. The research subjects were 8th-grade students of junior high schools in State 4 Metro. The sample in this study amounted to 72 respondents. Data collection techniques using the main techniques, namely questionnaires and tests as well as supporting techniques, namely interviews. Analysis of the research data is using SPSS version 25. Based on the results of the regression analysis which shows a significance value smaller than probability or 0.000 <0.05 and the percentage of influence is 55.1%, the hypothesis H0 is rejected and H1 is accepted. The results obtained indicate that there is a role for Pancasila and civic education teachers in implementing the Pancasila student profileKeywords: PPKn Teachers, Pancasila Student Profiles